A SOWER IN THE FIELD OF EDUCATION. DEDICATED TO THE 70TH ANNIVERSARY OF VASYL HRYHOROVYCH KREMEN, PRESIDENT OF THE NATIONAL ACADEMY OF PEDAGOGICAL SCIENCES OF UKRAINE - KONONENKO, VITALIY (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article is dedicated to the 70th anniversary of Vasyl Hryhorovych Kremen, Doctor of Philosophy, Academician of the National Academy of Sciences of Ukraine and the National Academy of Pedagogical Sciences of Ukraine, a prominent Ukrainian scholar, statesman and science manager. It highlights his main achievements and his great contribution to the development of Ukrainian education, and the development of Vasyl Stefanyk Precarpathian National University, where he was awarded Honorary Doctor’s Degree.